Vloga zakona v procesu komuniciranja prava - Štajnpihler Božič, Tilen (Slovenščina 2.0, 2025)
The starting point of this paper is the premise that the linguistic complexity of legislation, and specifically statutes, is one of the key factors that, in practice, hinders the effective exercise of rights granted by law. The paper therefore offers a concise analysis of the fundamental linguistic and structural features of a statute as a distinct type of legal text, including illustrative examples of how these features influence the linguistic (in)accessibility of statutes for their intended recipients. By presenting selected initiatives aimed at simplifying the language of statutes, the paper further highlights that concerns about linguistic accessibility have already, to some extent, been institutionalized within the legislative drafting process. However, even the most carefully considered textual modifications cannot eliminate all the inherent linguistic characteristics of statutes, which may continue to pose obstacles to their full accessibility for the average reader. Consequently, the paper concludes by adopting a theoretical framework that views law through the lens of communication, underscoring that legislation represents only a starting point within a broader societal process of conveying legal content. This shifts the focus of linguistic analysis from the statute itself to the question of how - and through which tools - the substance of the law as a source of legal norms can be effectively communicated.
Keywords: jezikovna dostopnost; komuniciranje prava; legal communication; legal knowledge; legal language; legislation; linguistic accessibility; pravna vednost; pravni jezik; zakon